2022
DOI: 10.1186/s12891-022-05522-3
|View full text |Cite
|
Sign up to set email alerts
|

A finite element analysis on different bone cement forms and injection volumes injected into lumbar vertebral body in percutaneous kyphoplasty

Abstract: Background To investigate the stress changes between different bone cement forms and injection volumes in adjacent vertebrae after percutaneous kyphoplasty (PKP) by establishing a three-dimensional finite element model of osteoporosis. Methods A male healthy volunteer was selected. CT of scans L1 to L3 vertebrae were imported into Mimics 21.0 software.The vertebral model of osteoporosiswas established based on previous literature reference. The mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 34 publications
(29 reference statements)
0
9
0
Order By: Relevance
“…Zhang et al reported the injection volume of bone cement also affects the stress on adjacent segments, this prompts us to conduct further study to optimize the use of silk hydrogel. [63] FEA results further suggested the uniform stress dispersion of silk gel scaffold compared with PMMA and osteoporotic trabecula (Figure 4e). Trabecular bone filled with silk demonstrated a decrease in peak stress by about 38-50% under the same compressive deformation loading condition.…”
Section: Mechanical Properties Of Vertebra Filled With Silk Gel Scaff...mentioning
confidence: 82%
See 1 more Smart Citation
“…Zhang et al reported the injection volume of bone cement also affects the stress on adjacent segments, this prompts us to conduct further study to optimize the use of silk hydrogel. [63] FEA results further suggested the uniform stress dispersion of silk gel scaffold compared with PMMA and osteoporotic trabecula (Figure 4e). Trabecular bone filled with silk demonstrated a decrease in peak stress by about 38-50% under the same compressive deformation loading condition.…”
Section: Mechanical Properties Of Vertebra Filled With Silk Gel Scaff...mentioning
confidence: 82%
“…Zhang et al reported the injection volume of bone cement also affects the stress on adjacent segments, this prompts us to conduct further study to optimize the use of silk hydrogel. [ 63 ]…”
Section: Resultsmentioning
confidence: 99%
“…Although finite element computational studies of the biomechanics of VCF repair was not the focus of this review, some remarks should be made. Great improvements in computational tools in recent years have encouraged some researchers to utilize finite element models, rather than costly experiments to investigate VCF treatments [12,39,[56][57][58][59][60][61][62][63][64][65][66][67][68]. However, the best way to model VCF fixation is still a controversial topic.…”
Section: Coil Implantmentioning
confidence: 99%
“…The cancellous region around the cement and/or implant can often be compacted during VCF treatment, which can alter the mechanical stresses on surrounding structures [60]. The vertebral bone is commonly modeled as osteoporotic to mimic older patients [65][66][67][68], but normal bone quality can also be easily simulated if younger patients are of concern. The shape, size, and material of the implant itself can be optimized [39,64], while the implant can be used alone or combined with other spine fusion devices [65].…”
Section: Coil Implantmentioning
confidence: 99%
See 1 more Smart Citation